Revealed beliefs and the marriage market return to education - Alison Andrew; Abi Adams (Institute for Fiscal Studies (IFS), 2022)
This paper develops a new methodology to analyze how parents in Rajasthan, India make choices about their daughters' schooling and marriage. We specify a dynamic discrete choice model in which parents face uncertainty about the quality of their daughter's future marriage offers. Parents' choices are thus partially driven by their beliefs about the likelihood of receiving high-quality marriage offers in the future and how this varies with age and education. We identify this model by creating a hypothetical-choice tool that enables us to identify preferences and probabilistic beliefs without directly eliciting probabilities. Parents perceive a significant marriage-market return to girls' education and this drives much of their investment in their daughters' schooling. While parents would prefer to delay a daughters' marriage until at least age 18, a belief that marriage-market prospects quickly deteriorate with age once a daughter is out of school creates an incentive to accept early marriage offers.
Keywords: 330; Educational attainment; Educational investment; Marriage; Discrete choice; Parents; Girls; Rural areas; India; Bildungsniveau; Bildungsinvestition; Ehe; Diskrete Entscheidung; Eltern; Mädchen; Ländlicher Raum; Indien